Ecosystem management: A management view - Lars J. Ravn-Jonsen (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2009)
The need for management of the marine ecosystem using a broad perspective has been recommended under a variety of names. This paper uses the term Ecosystem Management, which is seen as a convergence between the ecological idea of an organisational hierarchy and the idea of strategic planning with a planning hierarchy-with the ecosystem being the strategic planning level. Management planning requires, in order to establish a quantifiable means and ends chain, that the goals at the ecosystem level can be linked to operational levels; ecosystem properties must therefore be reducible to lower organisational levels. Emergence caused by constraints at both the component and system levels gives rise to phenomena that can create links between the ecosystem and operational levels. To create these links, the ecosystem's functional elements must be grouped according to their functionality, ignoring any genetic relation. The population structure is below the ecosystem in terms of the planning level, and goals for the community's genetic structure cannot be meaningful defined without setting strategic goals at the ecosystem level for functional groups.
Keywords: 330; Umweltökonomik; Meeresnutzung; Strategisches Management; Umweltmanagement; Theorie